(untitled) (Italiano LinguaDue, 2023)
Dopo una contestualizzazione teorica volta a problematizzare l’approccio al tema della correzione, l’articolo presenta i risultati di una ricerca condotta tramite questionario online rivolto a docenti di scuola primaria. Alla ricerca hanno partecipato 200 docenti del territorio italiano rispondendo a 48 quesiti finalizzati a raccogliere informazioni sulle pratiche didattiche di correzione. I risultati evidenziano che si tratta di un campione di docenti esperti, propensi a considerare la correzione come una pratica che può emergere in diversi momenti del processo di scrittura in forme non solo scritte ma anche orali e partecipate. I docenti del campione, inoltre, considerano necessario adattare le modalità di correzione a seconda delle caratteristiche dei singoli alunni e ritengono che lo scopo della correzione sia piuttosto accompagnare i bambini a scrivere un testo più corretto che procedere a una valutazione. To correct and not to correct. Teaching practices declared by primary school teachers After a theoretical introduction aimed at problematising the approach to the topic of correction, the article presents the results of a research conducted by means of an online questionnaire addressed to primary school teachers in Italy. 200 teachers participated in the research by answering 48 questions aimed at gathering information on correction practices. The results show that the respondents are a group of experienced teachers, inclined to consider correction as a practice that can emerge at different moments during the writing process not only in written but also in oral and participatory forms. The teachers in the sample also consider it necessary to adapt their correction methods according to the characteristics of the individual pupils and believe that the purpose of correction is rather to support the children in writing a more correct text than to proceed to an evaluation.